Multiple Choice Items: Tests and Usage - yorina ang'una bansa (English Literature Department, Adab and Humanities Faculty, 2020)
Multiple choice is one of the tool to test language skills especially reading and listening. Multiple choice is commondly use to evaluate students’ knowledge and performance. Sometimes it is not only for students but also for applicants or even workers. Thus, this study attempts to investigate what multiple choice items is and how it is used. The writer sees a need to carry out this study as it provides a platform to discover pedagogical implications that would benefit the teachers in terms of improving their knowledge and skill to know furher and be able to construct multiple choice items.